Western-style diet modulates contractile responses to phenylephrine differently in mesenteric arteries from senescence-accelerated prone (SAMP8) and resistant (SAMR1) mice - Jiménez-Altayó, Francesc; Onetti, Yara; Heras, Magda; Dantas, Ana P.; Vila, Elisabet (AGE, 2013)
The influence of two known cardiovascular risk factors, aging and consumption of a high-fat diet, on vascular mesenteric artery reactivity was examined in a mouse model of accelerated senescence (SAM). Five-month-old SAM prone (SAMP8) and resistant (SAMR1) female mice were fed a Western-type high-fat diet (WD; 8 weeks). Mesenteric arteries were dissected, and vascular reactivity, protein and messenger RNA expression, superoxide anion (O 2 ·− ) and hydrogen peroxide formation were evaluated by wire myography, immunofluorescence, RT-qPCR, ethidium fluorescence and ferric-xylenol orange, respectively. Contraction to KCl and relaxation to acetylcholine remained unchanged irrespective of senescence and diet. Although similar contractions to phenylephrine were observed in SAMR1 and SAMP8, accelerated senescence was associated with decreased eNOS and nNOS and increased O 2 ·− synthesis. Senescence-related alterations were compensated, at least partly, by the contribution of NO derived from iNOS and the enhanced endogenous antioxidant capacity of superoxide dismutase 1 to maintain vasoconstriction. Administration of a WD induced qualitatively different alterations in phenylephrine contractions of mesenteric arteries from SAMR1 and SAMP8. SAMR1 showed increased contractions partly as a result of decreased NO availability generated by decreased eNOS and nNOS and enhanced O 2 ·− formation. In contrast, WD feeding in SAMP8 resulted in reduced contractions due to, at least in part, the increased functional participation of iNOS-derived NO. In conclusion, senescence-dependent intrinsic alterations during early stages of vascular senescence may promote vascular adaptation and predispose to further changes in response to high-fat intake, which may lead to the progression of aging-related cardiovascular disease, whereas young subjects lack the capacity for this adaptation.